THE ROLE OF DIGITAL NUTRITION INFORMATION ACCESS IN SUPPORTING STUNTING PREVENTION: A SYSTEMATIC LITERATURE REVIEW - Alfi Rahmatillah Nur Fithriah (PRIMA WIYATA HEALTH, 2026)
Background: Stunting remains a critical global public health challenge requiring innovative and scalable solutions. The rapid development of digital technologies offers a promising approach to strengthening nutrition communication and health promotion. However, systematic evidence specifically examining the role of digital nutrition information in supporting stunting prevention remains fragmented. Objective: This study aimed to systematically evaluate the role of digital nutrition information access in supporting stunting prevention. Design: Systematic Literature Review (SLR) conducted in accordance with the PRISMA 2020 guidelines and registered in PROSPERO (CRD402612345). Data Sources: Electronic databases: PubMed, ScienceDirect, Google Scholar, and Garuda. Literature search was conducted in January 2026 for studies published between 2016 and 2026. Review A total of 300 records were identified. After duplicate removal, title/abstract screening, and full-text eligibility assessment, 13 original research articles met the inclusion criteria. Methodological quality was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Tools and Cochrane Risk of Bias 2 (RoB 2). Findings were synthesized using a narrative synthesis because of heterogeneity across interventions and outcomes. Results: Thirteen studies evaluated various digital interventions including mobile applications (38.5%), educational videos (23.1%), online learning platforms (15.4%), SMS (15.4%), and social media campaigns (7.6%). Eleven studies reported significant improvements in maternal nutrition knowledge, ten demonstrated improved complementary feeding practices, and eight showed protective effects against growth faltering. Mobile application interventions were associated with a 22% reduction in stunting risk (RR = 0.78). Conclusion: Digital nutrition information has the potential to contribute to stunting prevention by improving maternal nutrition literacy and optimal child-feeding practices. However, digital interventions should complement—not replace—comprehensive multisectoral public health strategies and investments in digital infrastructure to reduce inequities in access and achieve sustainable improvements in child growth.